Studies on Fruit Development in Pink and White types of Wax Apple (Syzygium samarangense Merr. & Perry) in Goa, India - Priya Devi S (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2020)
Fruit development studies were taken up in white and pink types of wax apple trees aging twelve years old at Goa, India. The study was initiated with the onset of flowering in November during the year 2018. After tagging the flowers on anthesis, samples were drawn periodically to record parameters like fruit weight, fruit volume, fruit length and diameter (upper, middle and lower), quality or biochemical parameters like total acids and sugars. Relative growth rate (RGR) was calculated for all parameters and graphs were generated. In both the types, fruit weight, fruit volume, fruit length and diameter increased in a sigmoidal pattern. The quality characters like TSS, total acids and total sugars also showed a sigmoidal pattern of increase whereas the increase in reducing sugars exhibited a double sigmoidal pattern of increase. It was evident from the curves that there was pronounced peak in growth rate between 21 and 28 days after anthesis for fruit weight, fruit volume, fruit length and diameter, in both pink and white types of wax apple.